Urinary retention presenting as complete bowel obstruction - Papeš, Dino; Altarac, Silvio; Arslani, Nuhi; Rajković, Zoran (Canadian Urological Association Journal, 2013)
A 59-year-old male was admitted to hospital for clinical and radiological signs of large bowel obstruction with clinical signs of generalized peritonitis. As such, he was scheduled to undergo emergency exploratory laparotomy. During preoperative preparation, over 2000 mL of urine was obtained after catheterization. We suggested re-evaluation, and after several hours the symptoms resolved. Although rare, pressure from the distended bladder due to urinary retention can cause complete bowel obstruction and signs of peritonitis. If a large volume of urine is obtained during preoperative preparation for mechanical bowel obstruction, it is recommended to re-evaluate the patient to avoid unnecessary surgery and imaging studies.